Problematising Multiculturalism in Canadian Literature - Šlapkauskaitė, Rūta (Literatūra, 2015)
The present article addresses the problem of multiculturalism in Canadian literature. While focusing on the major concerns of Canadian critical discourse on multiculturalism and ethnic minority writing, this theorising of Canadian multicultural literature highlights three areas of research – the definition of the notion, studies of postcolonialism and postmodernism and the simulative character of literary politics – that have been instrumental in conceptualising our understanding of Canadian multiculturalism and its reflections in literary texts. Alongside the theoretical observations about the problematic nature of the dominant forms of literary criticism on Canadian multiculturalism, the article offers a hypothesis of the multicultural aesthetic as a system of recurrent tropes that construct our reception of multicultural writing. Eventually, to illustrate the ambivalences of the multicultural aesthetic in Canadian literature, the article provides a brief reading of Anita Rau Badami’s novel Tamarind Mem as an example of the simulated multicultural exotic.